PENINGKATAN MOTIVASI BELAJAR ANAK MELALUI METODE FUN TEACHING - Ni Made Sulastri, (Jurnal Cahaya Mandalika ISSN 2721-4796 (online), 2023)
The world of education cannot be separated from the role of learning technology, in the learning process, a teaching and learning atmosphere must be created, so that it can motivate students to always study well and enthusiastically. Fun methods are needed to increase student learning motivation so that it can be increased, educators are required to carry out learning innovations that are effective, efficient, innovative and fun to attract children so that learning material will be accepted by early childhood. This study aims to describe the process and learning outcomes in the application of fun teaching activities to increase learning motivation. The research model used is the Kemmis and Taggart model with the research subjects being children at Darul Muhsinin Kindergarten. Data collection techniques were carried out through observation, interviews and documentation. The data analysis technique used in this research is qualitative and quantitative data analysis. Quantitative data analysis used to determine the percentage increase in children's gross motor skills after the action. Qualitative analysis is used to explain the research results. The results showed an increase in children's learning motivation after giving fun teaching activities through the research cycle. The implication of this research is that early childhood learning processes need to use strategies for fun teaching activities that can be considered as a medium to increase learning motivation.